The The Role Of Digital Marketing Capabilities And Service Innovation On Marketing Performance Through Customer Relationship Quality (An Empirical Study of Food and Beverage MSMEs in Pontianak) - Huang, Karnitasari; Heng, Lie; Stivenes, Stivenes (Amkop Management Accounting Review (AMAR), 2025)
This study aims to examine the role of digital marketing capabilities and service innovation on marketing performance, with customer relationship quality as a mediating variable, in Micro, Small, and Medium Enterprises (MSMEs) in the food and beverage sector in Pontianak City. A descriptive quantitative method was employed, with data collected through questionnaires distributed to business owners who actively use social media accounts. The data were analyzed using Structural Equation Modeling (SEM) with the AMOS software to assess the relationships among the variables. The results indicate that digital marketing capabilities do not have a significant direct effect on marketing performance. In contrast, service innovation and customer relationship quality have a significant direct influence on marketing performance. As a mediator, customer relationship quality plays a critical role in the relationship between service innovation and marketing performance but does not mediate the relationship between digital marketing capabilities and marketing performance. It is recommended that MSMEs enhance their service innovation and consistently maintain the quality of their customer relationships to achieve the desired marketing performance.